Enhanced phosphatidylserine exposure and erythropoiesis in Babesia microti-infected mice - Song, Peng; Cai, Yu-Chun; Chen, Mu-Xin; Chen, Shao-Hong; Chen, Jia-Xu (Frontiers in Microbiology, 2023)
Babesia microti (B. microti) is the dominant species responsible for human babesiosis, which is associated with severe hemolytic anemia and splenomegaly because it infects mammalian erythrocytes. The actual prevalence of B. microti is thought to have been substantially underestimated. In this study, Bagg’s albino/c (BALB/c) mice were intraperitoneally injected with B. microti-infected erythrocytes, and parasitemia was subsequently measured by calculating the proportion of infected erythrocytes. The ultrastructure of infected erythrocytes was observed using scanning and transmission electron microscopes. Quantifying phosphatidylserine (PS) exposure, oxidative stress, intracellular Ca2+, and erythropoiesis of erythrocytes were done using flow cytometry. The physiological indicators were analyzed using a Mindray BC-5000 Vet automatic hematology analyzer. Of note, 40.7±5.9% of erythrocytes changed their structure and shrunk in the B. microti-infected group. The percentage of annexin V-positive erythrocytes and the levels of reactive oxygen species (ROS) in the erythrocytes were higher in the B. microti-infected group than in the control group at 10 dpi. Significant splenomegaly and severe anemia were also observed following B. microti infection. The parasitemia level in the B. microti-infected splenectomized group was higher than that of the B. microti-infected sham group. The population of early erythroblasts increased, and the late erythroblasts decreased in both the bone marrow and spleen tissues of the B. microti-infected group at 10 dpi. PS exposure and elevated ROS activities were hallmarks of eryptosis in the B. microti-infected group. This study revealed for the first time that B. microti could also induce eryptosis. At the higher parasitemia phase, the occurrence of severe anemia and significant changes in the abundance of erythroblasts in B. microti-infected mice group were established. The spleen plays a critical protective role in controlling B. microti infection and preventing anemia. B. microti infection could cause a massive loss of late erythroblasts and induce erythropoiesis.